2013
DOI: 10.1371/journal.pgen.1003376
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing and Subfunctionalization Generates Functional Diversity in Fungal Proteomes

Abstract: Alternative splicing is commonly used by the Metazoa to generate more than one protein from a gene. However, such diversification of the proteome by alternative splicing is much rarer in fungi. We describe here an ancient fungal alternative splicing event in which these two proteins are generated from a single alternatively spliced ancestral SKI7/HBS1 gene retained in many species in both the Ascomycota and Basidiomycota. While the ability to express two proteins from a single SKI7/HBS1 gene is conserved in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 44 publications
2
80
0
Order By: Relevance
“…Other examples of duplicate genes retained and evolving to resemble ancestral alternative splicing isoforms preceding gene duplication are characterized in the MITF [55], FoxP [56] and Syn-Timp families [57]. Moreover, two genome-wide studies have shown that alternatively spliced genes are more likely to be found as duplicate copies in vertebrates [58] and fungi [59].…”
Section: Alternative Splicing Functional Innovation and The Evolutiomentioning
confidence: 99%
“…Other examples of duplicate genes retained and evolving to resemble ancestral alternative splicing isoforms preceding gene duplication are characterized in the MITF [55], FoxP [56] and Syn-Timp families [57]. Moreover, two genome-wide studies have shown that alternatively spliced genes are more likely to be found as duplicate copies in vertebrates [58] and fungi [59].…”
Section: Alternative Splicing Functional Innovation and The Evolutiomentioning
confidence: 99%
“…In general, functional divergence has been proposed to occur via changes in gene expression patterns at the transcriptional level (Force et al, 1999;Hittinger and Carroll, 2007;Gagnon-Arsenault et al, 2013) as well as changes in biochemical function. The primary mechanisms responsible for divergence in biochemical function among paralogs include site-specific regulatory modification of proteins (Marques et al, 2008;Freschi et al, 2011), variation of splicing sites among isoforms (Marshall et al, 2013;Nguyen Ba et al, 2014), and changes in enzymatic activity and protein specificity (Force et al, 1999;Voordeckers et al, 2012). Thus, analyzing key amino acids or functional motifs related to functional divergence could help reconstruct the evolutionary process of paralogs to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in S. cerevisiae the intronic genes are highly expressed and account for >70% of its proteome; in addition, several intron sequences are known to be duplicated within ribosomal protein paralogs Juneau et al 2006). Conversely, in Schizosaccharomyces pombe (an organism with ∼5000 genes) there are ∼5000 introns spreading over one-third of its genome, with up to 20 introns mediating a single gene (Wood et al 2002) and with few known genes displaying AS (Habara et al 1998;Okazaki and Niwa 2000;Marshall et al 2013). Other fungi such as Aspergillus nidulans and Candida albicans show variations in intronic characteristics as well (Kupfer et al 2004;Mitrovich et al 2007).…”
Section: Introductionmentioning
confidence: 99%